Depositional environment of shales and enrichment of organic matters of the Lower Cambrian Niutitang Formation in the Upper Yangtze Region - Xue Yang; Yue Lei; Jinchuan Zhang; Shijing Chen; Liqing Chen; Kesu Zhong; Liang He; Dingyuan Li; Qiuzi Wu (Natural Gas Industry B, 2021)
The Niutitang Formation in the Upper Yangtze Region comprises a set of the Early Cambrian black shales containing abundant organic matter. We investigated the relationship between the depositional environment and organic matter enrichment based on core description, slice observation, and geochemical analysis of the main trace elements. Additionally, we reconstructed the depositional environment of the Lower Cambrian Niutitang Formation shales and analyzed the main factors controlling the organic matter enrichment of shales during different deposition periods. According to the division of lithofacies, seven types of lithofacies have been identified in the Niutitang Formation. It is believed that the Niutitang Formation in northern Guizhou comprises a set of silicon-rich shales deposited on the continental shelf slope and formed under the control of different hydrodynamic forces. The main factors controlling its formation mechanism changed many times, from the initial hydrothermal deposition and enrichment controlled by oxygen deficiency to the enrichment accelerated by the high productivity at the surface of the water body. Subsequently, the change in sea level caused the change in the sea depth, which made it difficult for lower productivity to promote organic matter enrichment. Multiple main factors cooperated with the evolution of the depositional environment and jointly controlled the formation and distribution of organic-rich shales.